OBSERVACIONES SOBRE ALGUNAS FLORAS DEL CARBONIFERO ARGENTINO (Ameghiniana, 2013)
A preliminary critica! study of the sedimentary sequence established b>: ~renguel}1 .m the so~thern sector of the Sierra de Maz (La Rioja ), is made. Also de paleof~onstlc assoc~atlOn.found m the sequence is reported. It is concluded that the Guandacol ar:d Tupe forrnations mte~rate a sedimentary cycle of probably Carboniferous age. The same age 1Ssuspected for the floristic elements found in the quebrada de la Chavela (San Juan). Finally a brief examination of ~he fossil flora from Cienaga del Vallecito (San Juan) allows to establish an Upper Carboniferous age for the sediments outcropping in that area.